"I Live Quite a Good Balanced Life": A Pilot Study on the Life Experiences of Ageing Individuals Living with HIV. (17th June 2012) - Ribeiro Nobre, Nuno; Kylmä, Jari; Kirsi, Tapio
Abstract : An ageing population is accompanied by an increased number of older adults living with HIV. So far, our knowledge regarding the life experiences of older adults living with HIV is still poor and under researched. The purpose of this study is to present new knowledge by interviewing nine Finnish HIV-positive individuals of 50 years of age and older. The data were analysed by inductive content analysis. Living with HIV is shaped by unique personal life experiences. These experiences played an important role on how the interviewees assessed their lives and their future as HIV positive individuals. Most of the participants reacted negatively to their HIV-positive diagnosis. However, throughout time they had found meaning in their lives and had developed a degree of positive attitude towards life and future which was articulated in terms of a good overall balanced life. Since caring is the tenor of the nursing profession, nurses should be able to identify and implement methods for assessing how successfully older adults living with HIV age and intervene in an informed way whenever needed.